Fitogeografía de ecosistemas secos en la meseta de ignimbritas de Guanacaste, Costa Rica - Vargas Ulate, Gilbert (Universidad de Costa Rica, 2001)
The dry ecosystems in the ignimbrite meseta of Guanacaste, northwest Costa Rica is mapped. Plant community distribution is intimately related to the type of relief, soils and humidity. In the upper parts of the meseta, characterised by soils which are stony, sandy, and acidic, herbacious vegetation such as savanna and edaphic steppe is dominant. By contrast,woodland is found on the deep and organically rich soils of the valley floors. Within the herbaceous formations dwarf varieties of Byrsonima crassifolia (nance), Curatella americana (raspa guacal) and Quercus oleoides (encino) are found because of the acid and infertile soils.